Materials and the environment : eco-informed material choice - Ashby, M. F. (Butterworth-Heinemann, an imprint of Elsevier, 2021)
Materials and the Environment, Third Edition, discusses the history of our increasing dependence on materials and energy. The book explains where materials come from and how they are used in a variety of industries, along with their lifecycle and relationship to energy and carbon. In addition, it covers the controls and economic instruments that hinder the use of engineering materials, considers sustainability from a materials perspective, and highlights the importance of low-carbon power and material efficiency. Further sections cover the mechanical, thermal and electrical properties of engineering metals, polymers, ceramics, composites and natural materials and their relationship to environmental issues. This book is intended for instructors and students of Engineering, Materials Science and Industrial/Product Design, as well as for materials engineers and product designers who need to consider the environmental implications of materials in their designs.
Previous edition: Amsterdam: Elsevier/Butterworth-Heinemann, 2013.
Keywords: Materials -- Environmental aspects.; elektronické knihy; electronic books